Найти производную y=x^2(x-3) y=(x^3-2)(2x^3+1) y=x^3(3x+2) y=(3x^2-4)(7x^2+x-1)

0 голосов
27 просмотров

Найти производную y=x^2(x-3)
y=(x^3-2)(2x^3+1)
y=x^3(3x+2)
y=(3x^2-4)(7x^2+x-1)


Математика (71 баллов) | 27 просмотров
Дан 1 ответ
0 голосов

Y=(x^3-2)(2x^3+1)
y'= 
(x^3-2)'(2x^3+1)+(x^3-2)(2x^3+1)'=3x^2(2x^3+1)+(x^3-2)6x^2=6x^5+3x^2+6x^5-12x^2=12x^5-9x^2

(683 баллов)
0

Последний можете решить ?

0

могу

0

y'=(3x^-4)(7x^2+x-1)'=3*2x(7x^2+x-1)+(3x^2-4)(7*2x+1)=6x(7x^2+x-1)+(3x^2-4)(14x+1)=42x^3+6x^2-6+42x^3-56x+3x^2-4=84x^3+9x^2-56x-10

0

y'=((x^3)(3x+2))'=(3x^4+2x^3)'=3*4x^3+2*3x^2=12x^3+6x^2